2016
DOI: 10.1111/tri.12882
|View full text |Cite
|
Sign up to set email alerts
|

Immunological diversity in phenotypes of chronic lung allograft dysfunction: a comprehensive immunohistochemical analysis

Abstract: SUMMARYChronic rejection after organ transplantation is defined as a humoral-and cell-mediated immune response directed against the allograft. In lung transplantation, chronic rejection is nowadays clinically defined as a cause of chronic lung allograft dysfunction (CLAD), consisting of different clinical phenotypes including restrictive allograft syndrome (RAS) and bronchiolitis obliterans syndrome (BOS). However, the differential role of humoral and cellular immunity is not investigated up to now. Explant lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 31 publications
5
63
0
Order By: Relevance
“…Clinical research showed us that the percentage of lymphocytes and neutrophils increased and the percentage of macrophages reduced in BALF of patients with OB [228]. This is similar with the reports, which suggest an involvement of neutrophils in OB from both Vandermeulen et al and Eckrich et al [229, 230]. Tiriveedhi et al reported that neutrophil can participate in the obliterative airway disease and cause the early injury after passive transfer of CD8+ T cells [231].…”
Section: Neutrophils Participate In Other Respiratory Diseasessupporting
confidence: 73%
“…Clinical research showed us that the percentage of lymphocytes and neutrophils increased and the percentage of macrophages reduced in BALF of patients with OB [228]. This is similar with the reports, which suggest an involvement of neutrophils in OB from both Vandermeulen et al and Eckrich et al [229, 230]. Tiriveedhi et al reported that neutrophil can participate in the obliterative airway disease and cause the early injury after passive transfer of CD8+ T cells [231].…”
Section: Neutrophils Participate In Other Respiratory Diseasessupporting
confidence: 73%
“…Other studies focused on particular (inflammatory) cytokines and chemokines. lymphoid follicles, which is a common finding in other chronic respiratory diseases (62). Given this presence of lymphoid follicles, it comes as no surprise that immunoglobulin levels were also increased in rCLAD (63).…”
Section: Risk Factors and Mechanismsmentioning
confidence: 84%
“…[1][2][3][4] RAS is characterized by restrictive pulmonary physiology and persistent pleuroparenchymal abnormalities, such as peripheral ground-glass opacities, consolidation, traction bronchiectasis, architectural distortion, and (sub)pleural thickening on chest computed tomography (CT) scan. 12,13 Importantly, RAS carries an unfavorable prognosis with a median survival of 1-1.5 years after disease onset. 12,13 Importantly, RAS carries an unfavorable prognosis with a median survival of 1-1.5 years after disease onset.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, 3 patients were bridged to redo-transplantation with pirfenidone for 11 (5)(6)(7)(8)(9)(10)(11)(12) months and are currently alive, while 3 other patients demonstrate long-term stabilization of pulmonary function after 26.6 (range 18.4-46.6) months of treatment. We retrospectively assessed all lung transplant recipients with RAS who were treated with pirfenidone for at least 3 months (n = 11) in our lung transplant center and report on their long-term outcomes following initiation of pirfenidone.…”
mentioning
confidence: 99%